2016
DOI: 10.2147/clep.s103330
|View full text |Cite
|
Sign up to set email alerts
|

Using existing questionnaires in latent class analysis: should we use summary scores or single items as input? A methodological study using a cohort of patients with low back pain

Abstract: BackgroundLatent class analysis (LCA) is increasingly being used in health research, but optimal approaches to handling complex clinical data are unclear. One issue is that commonly used questionnaires are multidimensional, but expressed as summary scores. Using the example of low back pain (LBP), the aim of this study was to explore and descriptively compare the application of LCA when using questionnaire summary scores and when using single items to subgrouping of patients based on multidimensional data.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…In the single-stage LCA , all variables were entered into the analysis simultaneously. In the two-stage LCA , identical baseline variables had been used in a previous first stage LCA [ 27 ] to identify domain-specific patient categorisations within six domains of health (activity, contextual factors, pain, participation, physical impairment and psychology), and these categorical variables comprised the input to the second stage LCA. The descriptive comparison of the resulting patient subgroups from the single-stage and two-stage LCA was based on a combination of statistical performance measures, qualitative evaluation of clinical interpretability (face validity) and a subgroup membership comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the single-stage LCA , all variables were entered into the analysis simultaneously. In the two-stage LCA , identical baseline variables had been used in a previous first stage LCA [ 27 ] to identify domain-specific patient categorisations within six domains of health (activity, contextual factors, pain, participation, physical impairment and psychology), and these categorical variables comprised the input to the second stage LCA. The descriptive comparison of the resulting patient subgroups from the single-stage and two-stage LCA was based on a combination of statistical performance measures, qualitative evaluation of clinical interpretability (face validity) and a subgroup membership comparison.…”
Section: Methodsmentioning
confidence: 99%
“…LCA was performed within each of the health domains resulting in the six domain-specific patient categorisations. Based on the category for which their posterior probability was highest, patients were assigned to one of the categories within each health domain [ 27 ]. Subsequently, each category was given a descriptive label based on the main distribution of characteristics that distinguished each category from the others in the same health domain, using terms such as ‘more unemployed’, ‘higher BMI’ or by describing the span of the most frequently observed ages.…”
Section: Methodsmentioning
confidence: 99%
“…knowledge into the development process in addition to selecting potential prognostic factors and selecting the type of rule. A recent project using a systematic approach to develop clinically relevant subgroupings of low back pain patients based on a large set of potential prognostic factors, as well as patients, provides a unique opportunity to study this question [6,7]. In the process of developing these subgroupings, the outcome was not taken into consideration, hence, allowing us to check the prognostic capacity of the obtained groupings in an unbiased manner.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…After selecting a best-fit latent class model, individuals were assigned group membership based on highest posterior probability estimates. We reported that median posterior probabilities used to classify each individual (32). These values provide an indication of ambiguity surrounding subgroup membership, where probabilities close to one are preferable.…”
Section: Identification Of Comorbidity Subgroupsmentioning
confidence: 99%